2019
DOI: 10.1177/0957650919854583
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations on a new developed Savonius turbine for in-pipe hydro application

Abstract: Due to limitation of energy resources, a large body of research activities has been turned to investigate potential alternative avenues to supply energy. In this regard, the renewable sources, which can provide the sustainable and cleaner energy production, have increasingly become attractive. Hydropower has the highest proportion of the renewable energy sources. Availability and high efficiency are the undeniable advantages of the hydro potentials. In this paper, hydro-energy extraction from pipelines by a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It was determined that a 5blade turbine was the optimal blade configuration for hydropower harnessing and smoothing out torque ripples. Similarly, a numerical and experimental study on the same turbine showed the effects of the clearance, flow rate variation, head loss, and performance, where it was concluded that the optimal performance was obtained at a rotational speed of 50 / and with a 4 mm clearance, generating 55 and 20 of pressure drop [29]. Lastly, an analytical, numerical, and experimental study was developed on the drag-type modified Savonius turbines, where a parametric study was realized determining the optimal geometric dimensions of the turbine and the deflector, which guides the flow for the increase of turbine efficiency [30].…”
Section: Introductionmentioning
confidence: 95%
“…It was determined that a 5blade turbine was the optimal blade configuration for hydropower harnessing and smoothing out torque ripples. Similarly, a numerical and experimental study on the same turbine showed the effects of the clearance, flow rate variation, head loss, and performance, where it was concluded that the optimal performance was obtained at a rotational speed of 50 / and with a 4 mm clearance, generating 55 and 20 of pressure drop [29]. Lastly, an analytical, numerical, and experimental study was developed on the drag-type modified Savonius turbines, where a parametric study was realized determining the optimal geometric dimensions of the turbine and the deflector, which guides the flow for the increase of turbine efficiency [30].…”
Section: Introductionmentioning
confidence: 95%
“…Michell-Banki turbines without section pipe modifications reach efficiencies as high as 42.4 % [21,22]. Next comes the vertical-axis Savonius turbine with variable and constant curvature blades reaching efficiencies between 28% [23,24] and 45% [25], respectively. Then, the Darrieus type turbine is also used for this application, especially the straight-bladed Darrieus with 30% efficiency [26], the spherical with helicoidal blades with 26% [27], and the spherical Darrieus with 40% [25].…”
Section: Literature Review 121 Type Of Turbines For In-pipe Applicationsmentioning
confidence: 99%
“…The drag-type turbine, sometimes named the Savonius turbine, has also been successfully developed and utilized on different occasions. Payambarpour et al [22,23] performed a parametric study on a 3D modified Savonius turbine with a deflector in a 100 mm water pipe by using both experimental and numerical methods, where they found that the relationship between the flow rate and aspect ratio depended on the blockage coefficient. Chen et al [24] designed a drag-type vertical-axis hydro-turbine for pico-hydropower in water pipelines and conducted an optimization study based on previous design scheme.…”
Section: Introductionmentioning
confidence: 99%